Improving Mathematics and Science Education A Longitudinal Investigation of the Relationship Between Reform-Oriented Instruction and Student Achievement - Le, Vi-Nhuan (RAND Corporation, 2006)
Presents the findings of a multiyear study of the effectiveness of reform-oriented science and mathematics teaching (instructional practices for engaging students actively in their own learning and enhancing the development of complex cognitive skills)-specifically, whether such practices are associated with higher student achievement and whether that association is sensitive to the aspects of achievement that are measured. (CD-ROM enclosed.)